Reconstruction of the birth of a male sex chromosome present in Atlantic herring - Nima Rafati; Junfeng Chen; Amaury Herpin; Mats E. Pettersson; Fan Han; Chungang Feng; Ola Wallerman; Carl‐Johan Rubin; Sandrine Perón; Arianna Cocco; Mårten Larsson; Christian Trötschel; et al. (2020)
The mechanisms underlying sex determination are astonishingly plastic. Particularly the triggers for the molecular machinery, which recalls either the male or female developmental program, are highly variable and have evolved independently and repeatedly. Fish show a huge variety of sex determination systems, including both genetic and environmental triggers. The advent of sex chromosomes is assumed to stabilize genetic sex determination. However, because sex chromosomes are notoriously cluttered with repetitive DNA and pseudogenes, the study of their evolution is hampered. Here we reconstruct the birth of a Y chromosome present in the Atlantic herring. The region is tiny (230 kb) and contains only three intact genes. The candidate male-determining gene BMPR1BBY encodes a truncated form of a BMP1B receptor, which originated by gene duplication and translocation and underwent rapid protein evolution. BMPR1BBY phosphorylates SMADs in the absence of ligand and thus has the potential to induce testis formation. The Y region also contains two genes encoding subunits of the sperm-specific Ca2+ channel CatSper required for male fertility. The herring Y chromosome conforms with a characteristic feature of many sex chromosomes, namely, suppressed recombination between a sex-determining factor and genes that are beneficial for the given sex. However, the herring Y differs from other sex chromosomes in that suppression of recombination is restricted to an ∼500-kb region harboring the male-specific and sex-associated regions. As a consequence, any degeneration on the herring Y chromosome is restricted to those genes located in the small region affected by suppressed recombination.